1992
DOI: 10.1088/0954-3899/18/5/011
|View full text |Cite
|
Sign up to set email alerts
|

Is there an indication for the existence of right-handed weak currents in nuclear beta decay?

Abstract: We examine recent claims that experiments an neutron-decay are at variance with the standard V-A helicity structure of the standard model. The analysis presented here combines the neutron data with other recent experimental results and theoretical elaborations in the field of nuclear beta decay. If interpreted in the framework of left-right symmetric models, the data favour the existence of a right-handed weak gauge boson with mass between 207 and 369 GeV c2 at 95% CL. The fit using the standard V-A helicity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Both analyses were consistent with the V-A theory but allowed substantial deviations from it. Other adjustments realized later were either less general (Deutsch and Quin, 1995), excluded explicitly scalar and tensor contributions (Carnoy et al, 1992), or were limited to some specific decays (Abele, 2000;Towner and Hardy, 2003).…”
Section: Status Of the V-a Theorymentioning
confidence: 99%
“…Both analyses were consistent with the V-A theory but allowed substantial deviations from it. Other adjustments realized later were either less general (Deutsch and Quin, 1995), excluded explicitly scalar and tensor contributions (Carnoy et al, 1992), or were limited to some specific decays (Abele, 2000;Towner and Hardy, 2003).…”
Section: Status Of the V-a Theorymentioning
confidence: 99%
“…It is obvious, that erroneous estimation of the experimental accuracies or of the theoretical corrections could also lead to contradictions in the conclusions of the analyses. In fact, the report of the "low value" of the neutron decay asymmetry parameter AN [10] has led to a postulate of the right handed vector bosons Wn with a mass in the range of 200 -400 GeV/c 2 [13,14]. With the present, somewhat confused experimental situation, this interpretation turned out to be premature.…”
Section: Beyond the Standard Modelmentioning
confidence: 99%
“…A recent measurement of the electron asymmetry in the decay of polarized neutrons [1] has fostered speculation on the presence of right-handed currents in the semileptonic weak interaction [2,3] and new reports [4] of a possible unitarity violation in the quark-mixing matrix may also provide evidence of less than maximal parity violation. For simplicity, these deviations from the SM are interpreted in the context of the manifest left-right symmetric (MLRS) model [5], which introduces an additional, mainly righthanded charged gauge boson W2 to restore the parity symmetry of the weak interaction at sufficiently high energies.…”
mentioning
confidence: 99%
“…The parameters of this model are a mixing angle f, and 5, which is defined as d = M\/M2 where M\ and M2 are the masses of the observed, mainly left-handed, charged gauge boson IV\ and its heavy W2 counterpart. An analysis of the experimental data for several superallowed transitions [2] concluded that f must be small, in agreement with the results from the unitarity condition for the quark-mixing matrix, but that 5 was 2.5 standard deviations from zero, implying that M2 is in the range 210-320 GeV/c^ at 90% C.L. This result is in disagreement with MLRS analyses in the purely leptonic and hadronic sectors [6] and, if real, requires invoking more complex extensions of the SM [7] which are not manifestly symmetric.…”
mentioning
confidence: 99%
See 1 more Smart Citation